Implementing Program and Department Advisory Boards - Karen Blaisure PhD; Bryce Dickey MS; Linda Dove MA; John McElroy PhD (Academic Chairpersons Conference Proceedings, 2017)
Presenters will guide participants through a process to establish and maintain an advisory board for an academic program or department and will leave with ideas, suggestions, and a potential plan to share with faculty. Advisory board participation in assessment and improving academic curricula will be highlighted.
Keywords: advisory board; assessment; community collaboration; campus-community collaboration